2014
DOI: 10.3892/mmr.2014.2652
|View full text |Cite
|
Sign up to set email alerts
|

Silencing ADAM10 inhibits the in vitro and in vivo growth of hepatocellular carcinoma cancer cells

Abstract: Abstract.A disintegrin and metalloprotease 10 (ADAM10) is a transmembrane protein associated with metastasis in a number of types of cancer. Little is known, however, regarding the role of ADAM10 in hepatocellular carcinoma (HCC). The aim of the present study was to evaluate whether downregulation of ADAM10 effects HCC cell proliferation, cell cycle, cell migration and cell invasion. A recombinant small hairpin RNA expression vector carrying ADAM10 was constructed and then transfected into the HepG2 human HCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…established that downregulation of ADAM10 in HepG2 cells using RNA silencing significantly suppressed cell proliferation, migration, and invasion in vitro , and tumor growth in vivo . Furthermore, silencing ADAM10 decreased constitutive phosphorylation of phosphoinositide 3‐kinase (PI3K) and Akt, which indicates that ADAM10 is involved in the activation of the PI3K/Akt signaling pathway . In addition, Endres et al .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…established that downregulation of ADAM10 in HepG2 cells using RNA silencing significantly suppressed cell proliferation, migration, and invasion in vitro , and tumor growth in vivo . Furthermore, silencing ADAM10 decreased constitutive phosphorylation of phosphoinositide 3‐kinase (PI3K) and Akt, which indicates that ADAM10 is involved in the activation of the PI3K/Akt signaling pathway . In addition, Endres et al .…”
Section: Discussionmentioning
confidence: 98%
“…ADAM10 has been reported to be overexpressed in various malignancies and to be involved in cancer progression . For example, Liu et al . established that downregulation of ADAM10 in HepG2 cells using RNA silencing significantly suppressed cell proliferation, migration, and invasion in vitro , and tumor growth in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Silencing inhibits the in vitro and in vivo growth of hepatocellular carcinoma cells (Liu, Zhang, Liu, Ji, & Wang, ),…”
Section: A Brief History Of Earlier Studies Of Aneuploidy and Admentioning
confidence: 99%
“…6 In this study, we first demonstrated that EGCG induced HepG2 and PC12 apoptosis and regulated apoptosis-related proteins Bax and Bcl-2 expression. 12 These data indicated that EGCG induces tumour cells apoptosis via not only reduces APP, but also decreases ADAM10. 6 To our surprise, EGCG also decreased ADAM10 level, a member of the ADAM family involved in multiple cellular processes such as cell proliferation, differentiation, migration and invasion.…”
Section: Discussionmentioning
confidence: 85%